1992
DOI: 10.1073/pnas.89.21.10302
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response to elevated temperature in the symbiotic dinoflagellate Symbiodinium microadriaticum in culture.

Abstract: Elevated temperature (28-WC) has been hypothesized as the primary cause of the loss of algal endosymbionts in coral reef-associated invertebrates, a phenomenon observed on a world-wide scale over the last decade. In past studies of this "bleaching" phenomenon, there has been an underlying assumption that temperature adversely affects the animal hosts, the algae thereby being relegated to a more passive role. Because photosynthesis is a sensitive indicator of thermal stress in plants and has a central role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
279
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(296 citation statements)
references
References 22 publications
15
279
0
2
Order By: Relevance
“…In less than one hour of high temperature exposure, photosynthesis rates in cultured Symbiodinium microadriaticum increased at temperatures up to 30°C and decreased drastically above 30°C (Iglesias-Prieto et al 1992). The mitotic index (percent of cells dividing) in thermally stressed Symbiodinium cultures decreases within days of heat exposure (Bouchard and Yamasaki 2009).…”
Section: Numerous Biological Symptoms Of the Symbiodinium Thermal Strmentioning
confidence: 99%
“…In less than one hour of high temperature exposure, photosynthesis rates in cultured Symbiodinium microadriaticum increased at temperatures up to 30°C and decreased drastically above 30°C (Iglesias-Prieto et al 1992). The mitotic index (percent of cells dividing) in thermally stressed Symbiodinium cultures decreases within days of heat exposure (Bouchard and Yamasaki 2009).…”
Section: Numerous Biological Symptoms Of the Symbiodinium Thermal Strmentioning
confidence: 99%
“…Coral bleaching is a consequence of high-irradiance and high water temperatures (Iglesias-Prieto et al 1992;Jones et al 1998;Warner et al 1999Warner et al , 2002Mumby et al 2001). Recently, it has been shown that the interrelatedness of temperature and light has reciprocal effects, whereby the increase in temperature under high light conditions will be perceived by the symbionts as an increase in light stress, and vice versa (Iglesias-Prieto et al 2004;Takahashi et al 2004;Nakamura et al 2005).…”
Section: Palau's Reefs In Contextmentioning
confidence: 99%
“…In Symbiodinium isolated from the jellyfish Cassiopeia xamachana, photosynthesis is inhibited at temperatures above 30°C and completely disrupted at 34-36°C (7). Subsequent studies have shown that reduced photosynthesis caused by thermal stress in Symbiodinium can be attributed to photoinhibition of PSII (3,4).…”
mentioning
confidence: 99%